Uncertainty quantification of rock mass discontinuity information and mechanical parameter derived from photogrammetry and Monte Carlo simulation: A case study - Xiaoyu Yi; Wenkai Feng; Yongjian Zhou; Wenxuan Wu; Jiachen Zhao (Results in Earth Sciences)
The uncertainty of rock mass mechanical parameters primarily stems from the inherent inhomogeneity of rock mass materials and discontinuities. Traditional deterministic methods often overlook this uncertainty, potentially impacting overall design performance. To address this issue, the study introduces an uncertainty analysis framework based on Monte Carlo simulation (MCS). This framework probabilistically quantifies the Geological Strength Index (GSI) system by utilizing the digital characterization of rock mass discontinuity information derived from photogrammetry technology, and subsequently evaluates the uncertainty of rock mass mechanical parameters. The analytical framework was applied to assess the mechanical properties of the surrounding rock in an underground powerhouse located in Henan Province, China. The results demonstrate that the proposed framework is effective in evaluating these properties and provides valuable insights for the probabilistic assessment of excavation response and support measures in underground engineering.